Advancing diet reconstruction in fish eye lenses. Issue 3 (27th January 2021) - Bell‐Tilcock, Miranda; Jeffres, Carson A.; Rypel, Andrew L.; Sommer, Ted R.; Katz, Jacob V. E.; Whitman, George; Johnson, Rachel C.
Abstract: Tracking habitat use and dietary shifts in migratory species is vital to conservation and management. Yet, conventional animal tracking often precludes tracking small juveniles at critical life stages where recruitment bottlenecks often manifest. Stable isotope analysis (SIA) in consecutive laminae in eye lenses, a protein‐rich depositional tissue, has emerged as a promising tool in fishes to develop long‐term interpretive records of dietary histories using a single archival tissue. Currently, studies using fish eye lenses to study SIA in diets have primarily been conducted in marine environments using δ 13 C and δ 15 N to identify resource partitioning, ontogenetic shifts and lifelong trophic histories. To date, no studies have examined freshwater taxa nor used δ 34 S isotopes. We placed juvenile (Chinook Salmon) Oncorhynchus tshawytscha in experimental enclosures in three different freshwater habitats (hatchery, river and seasonal floodplain), each with isotopically distinct and well‐characterized food webs. This experimental approach allowed us to directly measure diets and quantify tissue turnover rates in eye lenses as well as the isotopic fractionation among fish tissues (fin and muscle tissue) in distinct habitat types using stable isotopes δ 13 C, δ 15 N and δ 34 S. Bulk eye‐lens stable isotope measurements were analysed for juvenile salmon lenses and were found to be consistent with the isotopic values of rearing habitats. Slight additional isotopic fractionation was only found in δ 13 C. We then successfully applied the method to a larger, reproductively mature adult salmon captured in freshwater and inferred juvenile habitat use. SIA in eye lenses using three dietary isotopes (δ 13 C, δ 15 N and δ 34 S) has significant potential for answering critical questions about migration, diet, foraging ecology and life history of migratory aquatic animals on Earth. Such information would have immediate application towards conservation management of diverse species and habitats at multiple scales.